PENGARUH MEDIA APLIKASI SITUS WEBTERHADAP HASIL BELAJAR PESERTA DIDIK KELAS IX PADA MATA PELAJARAN IPS DI SMP N 1 PALEMBANG - Suci Wulandari; Yulia Djahir; Fitriyanti Fitriyanti (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2014)
The purpose of this research is to know the difference of media application effect of website with microsoft powerpoint application to the learning result of class IX students in IPS subjects in SMP N 1 Palembang. The research is a type of Quasi Experimental Design research with nonequivalent Control Group Design. The population in this study is the students of class IX SMP N 1 Palembang odd semester of the academic year 2013/2014 consisting of 7 classes with the number of 212 students. The sample was taken by using cluster random sampling technique and got two classes that is class IX.1 as experiment class which amounted to 30 students and class IX.3 as control class which amounted to 30 students. Technique of collecting data is obtained by using learning result test and observation of learning activity. The statistics used to analyze the data in proof are parametric statistics through t-related tests (for paired samples) with a significance level of 5%, and degrees of freedom dk = n1 + n2 - 2 so (dk = 30 + 30 - 2 = 58) which means t_hitung> t_tabel = 3.14˃ 2.0021 then Ho is rejected and Ha accepted. The result of this research conclude that there is difference of influence of web application media with the powerpoint media toward the learning result of class IX students in social studies subject at SMP N 1 Palembang. It can be seen in the learning outcomes of IPS learners who are given media application web site is higher than the results of learning IPS learners who are given media powerpoint. Therefore, the media application of this website and media powerpoint can be used as an alternative for teachers in improving learners' learning outcomes.